Listening, reading, writing – which method leads to the best learning outcome? - Güldenpfennig, Janine; Bartel, Alexander; Arlt, Sebastian (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2023)
Objective Innovative teaching strategies such as case-based learning and hands-on training are more and more integrated into undergraduate veterinary teaching. Nevertheless, it can be assumed that lectures still play an important role in many vet schools. Nowadays, however, lectures are questioned to be motivating and engaging enough for a long-lasting learning retention. In this context, we compared acceptance and learning outcome of the teaching methods reading, writing, and listening to a presentation.Material and methods In structured settings based on a cross-over design, 151 students in their fifth year attending a 2-weeks clinical rotation at the Clinic for Animal Reproduction were asked to read papers, listen to a presentation by a lecturer, and to write a summary in group work. Each task dealt with 1 of 3 topics from the field of animal reproduction. A week later, the students were asked to complete a multiple-choice test and an evaluation form. The test contained questions about each of the covered topics as well as a fourth topic, which was not taught in context of this project to assess the students’ prior knowledge.Results The results revealed that writing a summary in group work led to the best learning outcome, but it cannot be ruled out that learning success may have depended to a large extent on group work. Furthermore, the results did not differ significantly from the second-best teaching method listening to a presentation. The teaching method students preferred most was the lecture, followed by reading papers and writing a summary.Conclusions We conclude that presentations by lecturers are still an important teaching method but can be complemented by writing tasks, which may be used in specific settings as a possible way to improve learning outcome in veterinary education.Conclusion for practice Our project supports the assumption that more active, student-centered learning approaches such as writing summaries can lead to more engagement and a better learning retention. In addition, training writing skills is important because clinical reports and other written communication are relevant parts of daily veterinary routine.
Keywords: Veterinary Medicine; veterinary education; teaching; lifelong learning; knowledge